A case of an abscessed cystic endometriotic lesion in the vesico-uterine pouch after oocyte retrieval - Shigeru Matsuda (Wolters Kluwer Medknow Publications, 2021)
A 31-year-old nulliparous Japanese woman visited the clinic due to worsening dysmenorrhea. A cystic endometriotic lesion was found in the vesico-uterine pouch. Laparoscopic surgery was chosen due to the severe dysmenorrhea. Her first oocyte retrieval attempt was performed at in-vitro fertilization clinic before the planned surgery. However, she complained of abdominal pain on day 6 after the retrieval. We diagnosed her with peritonitis with an abscessed cystic endometriotic lesion in the vesico-uterine pouch. Conservative treatment was ineffective. Therefore, laparoscopic surgery was performed. The cysts in the vesico-uterine pouch were drained of pus. No adhesions or lesions of endometriosis in the uterus, bilateral adnexa, or pelvic peritoneum were found. Although cystic endometriotic lesions in the vesico-uterine pouch are rare, they can form abscesses after oocyte retrieval. The possibility of abscesses formation risk must be considered. Moreover, following the management of endometrioma, sufficient medication should be administered to prevent this formation.